Cyberbiosecurity: An Emerging New Discipline to Help Safeguard the Bioeconomy - Murch, Randall S.; So, William K.; Buchholz, Wallace G.; Raman, Sanjay; Peccoud, Jean (Frontiers in Bioengineering and Biotechnology, 2018)
Cyberbiosecurity is being proposed as a formal new enterprise which encompasses cybersecurity, cyber-physical security and biosecurity as applied to biological and biomedical-based systems. In recent years, an array of important meetings and public discussions, commentaries and publications which have occurred that highlight numerous vulnerabilities. in various areas. While necessary first steps, they do not provide a systematized structure for effectively promoting advancing communication, education and training, elucidation and prioritization for analysis, research, development, test and evaluation and implementation of scientific, technological, standards of practice, policy, or even regulatory or legal considerations for protecting the bioeconomy. Further, experts in biosecurity and cybersecurity are generally not aware of each other’s domains, expertise, perspectives, priorities, or where mutually supported opportunities exist for which positive outcomes could result. Creating, promoting and advancing a new discipline can assist with formal, beneficial and continuing engagements. Recent key activities and publications that inform the creation of Cyberbiosecurity are briefly reviewed, as is the expansion of Cyberbiosecurity to include biomanufacturing which is supported by a rigorous analysis of a biomanufacturing facility. Recommendations are provided to initialize Cyberbiosecurity and place it on a trajectory to establish a structured and sustainable discipline, forum and enterprise.